1993
DOI: 10.1111/j.1476-5381.1993.tb13811.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excitatory neurotransmitters on Ca2+ channel current in smooth muscle cells isolated from guinea‐pig urinary bladder

Abstract: 1 A whole-cell voltage clamp technique was used to examine the effects of purinoceptor and muscarinic receptor agonists on voltage-sensitive Ca2" channels in guinea-pig isolated urinary bladder cells.2 When the cell membrane was clamped at the holding potential, rapid application of ATP elicited a large inward current in normal solution containing 2.5 mM Ca2", and reduced the subsequent Ca2c hannel current evoked by a depolarizing pulse (O mV). Carbachol (CCh) elicited little membrane current, but similarly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The results of both the diltiazem and low calcium studies support the concept that the cholinergic response involves both calcium influx and intracellular calcium release, whereas the purinergic response is mediated primarily if not exclusively by calcium influx. This concept is supported by a recent study performed on guinea pig urinary bladder by Nakayama [1993]. By using an intracellular recording technique, Nakayama [ 19931 has concluded that purinergic stimulation is mediated by the opening of non-selective cation channels.…”
Section: Discussionmentioning
confidence: 74%
“…The results of both the diltiazem and low calcium studies support the concept that the cholinergic response involves both calcium influx and intracellular calcium release, whereas the purinergic response is mediated primarily if not exclusively by calcium influx. This concept is supported by a recent study performed on guinea pig urinary bladder by Nakayama [1993]. By using an intracellular recording technique, Nakayama [ 19931 has concluded that purinergic stimulation is mediated by the opening of non-selective cation channels.…”
Section: Discussionmentioning
confidence: 74%
“…In detrusor smooth muscle, muscarinic agonists are known to release Ca 2ϩ from the intracellular stores via G protein activation and subsequent IP 3 formation (26,36). Figure 5 shows the effects of the IP 3 receptor antagonists heparin and xestospongin C (cell membrane-impermeable and -permeable IP 3 receptor antagonists, respectively) (9, 32).…”
Section: Resultsmentioning
confidence: 98%
“…Experiments on cultured smooth muscle cells from rabbit bladder, performed with the fura-2 technique to measure changes in intracellular Ca 2+ , showed that ATP produced a rapid but transient increase in [Ca 2+ ] i , while ACh produced a delayed, prolonged increase [534]. Studies on isolated smooth muscles cells from guinea-pig bladder, using a whole-cell voltage-clamp technique, confirmed that purinergic receptor stimulation opens nonselective cation channels, while muscarinic stimulation triggers Ca 2+ release from intracellular stores [512]. Different types of Ca 2+ channels are present prejunctionally and postjunctionally in the urinary bladder.…”
Section: Extracellular Calcium Calcium Channel Blockers and Potassiumentioning
confidence: 96%